Crises, Contagion, and the Closed : End Country Fund Puzzle - Levy Yeyati, Eduardo (IMF Working Papers; Working Paper, 1998)
This paper analyzes the behavior of closed-end country fund discounts, including evidence from the Mexican and East Asian crises. We find that the ratio of fund prices to their fundamental value increases dramatically during a crisis, an anomaly that we denote the 'closed-end country fund puzzle.' Our results show that the puzzle relates directly to the fact that international investors are less (more) sensitive to changes in local (global) market conditions than domestic investors. This asymmetry implies that foreign participation in local markets can both help dampen a crisis in the originating country, and amplify the contagion to noncrisis countries.